Conocimiento y aplicación de la mecánica corporal al movilizar pacientes, Hospital Belén de Trujillo - Bustamante Solano, Jessica Yesenia (2021)
The present quantitative, non-experimental, descriptive, correlational, crosssectional investigation was carried out with the objective of determining the relationship between the level of knowledge and the application of body mechanics when mobilizing patients from the Belén de Trujillo hospital. The sample universe consisted of 47 nurses to whom a questionnaire was applied to measure the level of knowledge and a checklist to identify the application of body mechanics, reaching the following results: 91.5 percent of nurses have a level of high knowledge about body mechanics, and 8.5 percent level of medium knowledge; 91.5 percent of nurses apply body mechanics adequately when mobilizing patients and 8.5 percent improperly. According to dimensions: when lifting objects, 68.1 percent apply body mechanics in an inappropriate way; and adequately in the dimensions when adopting the standing position 67.4 percent; when adopting the sitting position 80.9 percent; 87.2 percent when transporting patients and 51.1 percent when transporting patients; Concluding that there is a significant relationship between the level of knowledge of the nurse and the application of body mechanics when mobilizing patients, obtaining a Tau c of kendall = 0.311 Probability = 0.021.